SOCIO-ECONOMIC CHANGES IN THE COMMUNITY AMIDST THE DEVELOPMENT OF TOURISM IN SELOPANGGUNG VILLAGE, SEMEN DISTRICT, KEDIRI REGENCY - Kurnia, Aminatul; Mansur, Mochammad; Alamin, Taufik; Ningtyas, Trimurti (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Social change in society is a phenomenon where society will always move dynamically and is not in a static state. Changes will always be seen, with visible differences in society from time to time. Change is increasingly important if it is linked to economic development in a society, causing changes also in fields outside the economy, namely social and cultural, namely economic development through the tourism industry. Selopanggung Village is one of the villages with a lot of natural potential and is now being developed into several tourist attractions. The existence of tourism has had a lot of influence on local communities, causing changes in the socio-economic and cultural fields. The focus of this research is the process of change in society amidst tourism development and the forms of change that occur related to tourism development. This research approach uses qualitative research with a case study type of research. The research was carried out in Selopanggung Village, Semen District, Kediri Regency. The data obtained by researchers is a primary data source conducted through direct interviews with village governments, tourism managers, and local communities. Meanwhile, data collection methods include interviews, observation, and documentation. Data analysis uses the Miles and Huberman method, reducing data, displaying data, and drawing conclusions. The data validity technique uses the triangulation method to prove its truth. The results of this research concluded that the development of tourism in Selopanggung Village not only brought changes in the economic sector but also in the socio-cultural sector. The process of change goes through several processes to bring changes to the livelihood system. Where previously the main source of income was farming, now there are increasingly various types of livelihoods. Then changes in culture can be seen in changes in rituals, which are starting to shift; other social changes in the younger generation starting to follow clothing trends; decreasing interest in agricultural work; and also starting to become familiar with the culture of hanging out in cafes. This is due to the influence of contact with other cultures brought by tourists and investors from urban areas. The use of technology in society is also increasingly being used in daily activities. What influences this is that society wants to move forward and not be left behind by the progress of the times.